THE USE OF CANNABIDIOL IN THE TREATMENT OF ACNE (REMUNOM, 2025)
Acne is a disease that affects a large part of the population, and its treatment requires different strategies. Currently, the search for natural alternatives for topical treatments has grown worldwide. The Cannabis sativa plant became known for being used to obtain the sensations of excitement and relaxation that the substances from its flowers are capable of providing. One of these is Cannabidiol, a non-psychoactive compound that has several therapeutic properties. This study consisted of a review of the literature on the therapeutic effects of Cannabis sativa, especially cannabidiol (CBD), for the treatment of acne. The research was carried out using articles, theses and dissertations in the Scopus, PUBMED and Google Scholar databases. Studies indicate that Cannabidiol has anti-inflammatory activity on the skin and has the potential to be manipulated in the form of a topical cosmetic to prevent and combat acne caused by bacteria, without causing harm to the patient. Although its therapeutic activity has been confirmed, more studies on the active ingredient need to be carried out. Meanwhile, its use remains just a hope for future alternative acne treatments, given that the substance is part of a plant that is still criminalized.